Construction of machine learning models of lipid metabolism-related long non-coding RNA in lung adenocarcinoma is associated with microenvironmental heterogeneity and immunotherapy - Jiali Xiong; Kailan Xiao; Huiyang He; Yuqiu Tian (Discover Oncology)
Abstract Using various bioinformatics tools, we constructed a prognostic model integrating the expression profiles of lipid metabolization-related lncRNAs and clinical features. Our study discovered that various lipid metabolism-related lncRNAs were linked to the prognosis of lung adenocarcinoma. The link between immune cell infiltration in the tumour microenvironment and the expression level of lncRNAs involved with lipid metabolism was also investigated. Our findings suggest that there is a complex interplay between lipid metabolism, microenvironmental heterogeneity, and immunotherapy in lung adenocarcinoma. Furthermore, the study has significant clinical implications for the development of effective therapies for patients with lung adenocarcinoma by investigating the potential of these lncRNAs as biomarkers for anticipating the response to immunotherapy. Finally, our study emphasises the significance of continued analysis of lncRNAs associated with lipid metabolism in tumours to better understand the mechanisms behind the incidence and progression of lung adenocarcinoma. Several of the strengths of our work are the extensive analysis of the relationship between lipid metabolism and lncRNAs in lung adenocarcinoma and the utilization of a sizable sample size from the TCGA-LUAD cohort. However, there are also some limitations. Firstly, the mechanisms of how these lncRNAs interact with lipid metabolism pathways and immune response require further investigation. Secondly, our study was based on bioinformatics analysis and lacked experimental verification. Finally, our study was limited to the TCGA-LUAD cohort and further validation using other independent cohorts is required. In conclusion, our study provides a comprehensive and systematic analysis of lncRNAs associated with lipid metabolism in lung adenocarcinoma. Lung cancer patients may benefit from using identified lncRNAs as therapeutic targets and prognostic biomarkers. Validating these findings and confirming the potential therapeutic applications of these lncRNAs will require more mechanistic research.